Applied caligraphy & graphic design - Campedelli, Marco (Links, 2010)
Caligraphy differs from computer graphics because of its quality and unquestionable originality. This book contains projects by 23 professional caligraphers which demonstrate that calligraphy and hand-crafted graphics in general are the exclusive or primary medium for communication.